Comparison of the effects of nadolol and bisoprolol on the isoprenaline-evoked dilatation of the dorsal hand vein in man - Abdelmawla, A H (Blackwell Science Inc, 2001)
AIMS: We attempted to explore the possible differential involvement of β-adrenoceptor subtypes in the dilator response of the human dorsal hand vein to isoprenaline by examining the ability of bisoprolol, a selective β(1)-adrenoceptor antagonist, and nadolol, a nonselective β(1)/β(2)-adrenoceptor antagonist, to antagonize the response. METHODS: Twelve healthy male volunteers participated in four weekly sessions. In the preliminary session a dose-response curve to the vasoconstrictor effect of phenylephrine was constructed and the dose producing 50–75% maximal response was determined for each individual. In each of the remaining three (treatment) sessions, nadolol (40 mg), bisoprolol (5 mg) or placebo was ingested, and isoprenaline hydrochloride (3.33–1000 ng min(−1)) was infused locally into the dorsal hand vein along with a constant dose of phenylephrine hydrochloride (to preconstrict the vein) 2 h after the ingestion of the drugs. Changes in vein diameter were monitored with the dorsal hand vein compliance technique. Subjects were allocated to treatment session according to a double-blind balanced cross-over design. Systolic and diastolic blood pressure, and heart rate were also measured. RESULTS: Isoprenaline produced dose-dependent venodilatation which was antagonized by nadolol but remained unaffected by bisoprolol (anova with repeated measures: P < 0.025; Dunnett's test: placebo vs nadolol, P < 0.01; placebo vs bisoprolol, P = NS). Mean log ED(50) (ng min(−1)) was significantly increased in the presence of nadolol and remained unchanged in the presence of bisoprolol (anova, P < 0.025; Dunnett's test: placebo vs nadolol, P < 0.005; placebo vs bisoprolol, P = NS; differences between mean log ED(50) [95% CI]: placebo vs bisoprolol −0.11 [-0.38, 0.16], placebo vs nadolol 0.32[0.09, 0.72], bisoprolol vs nadolol −0.43 [-0.71, −0.15]). Mean E(max) did not differ in the three treatment conditions. CONCLUSIONS: The failure of bisoprolol to attenuate isoprenaline-evoked venodilatation in the human dorsal hand vein argues against the involvement of a β(1)-adrenoceptor-mediated component in the isoprenaline-evoked venodilatory responses. The possibility cannot be excluded that the consequences of β(1)-adrenoceptor blockade by bisoprolol might have been obscured by a possible venodilator effect of bisoprolol.